PEMBANGUNAN KORPORASI PERTAMBANGAN MELALUI PENDEKATAN AKUNTANSI LINGKUNGAN (STUDI KASUS PADA PROFITABILITAS PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Anindya, Desy Astrid; Habibie, Muhammad; Dalimunthe, Hasbiana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The purpose of this study was to determine the effect of environmental accounting and company size on profitability partially and simultaneously. The population in this study is the mining sub-sector companies as many as 42 companies with a sampling technique based on criteria using purposive sampling. The sample obtained based on the criteria of 15 mining sub-sector companies. This type of research is quantitative with a causal associative approach. The data analysis technique used is quantitative with descriptive statistics using SPSS v.25. The results of the study state that Environmental Accounting partially has a positive and significant effect on profitability and company size partially has a positive and significant effect on profitability.